Analisis Tindak Pidana Pengutipan Liar di Wisata Alam Lau Debuk-Debuk di Tinjau dari Hukum Pidana dan Pidana Islam: (Studi Kasus Desa Semangat Gunung Kecamatan Merdeka Kabupaten Karo) - Lina Wita Sigalingging; M.Rizal; Syaddan Dintara Lubis (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The aim of this research is to determine the application of sanctions for perpetrators of illegal levies in Spirit Mountain Village, Merdeka District, Karo Regency and to find out the obstacles in implementing sanctions for perpetrators of illegal levies in Spirit Gunung Village, Merdeka District, Karo Regency. This research is field research as supporting basic material for writing. This research uses an empirical juridical approach. The results of the research show that enforcement of the illegal quoting law in Spirit Mountain Village, Merdeka District, Karo Regency is an activity carried out because of community habits. That the practice of illegal quoting is not organized but has become a habit that is ultimately difficult to break. This habit also occurs because tourists and local residents also think this is normal. Then this act was assessed as normal by the community in the Criminal Code's view that illegal quoting practices that occur at tourist locations in the village of Lau Debuk-Debuk are prohibited. Regarding this matter, a sentence of 2 years in prison can be imposed in accordance with the mandate of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes which was amended by Law Number 20 of 1999. The Islamic Criminal Law's view of the practice of illegal quoting that occurred at a location in the Spirit Mountain Village, Merdeka District, Karo Regency is considered an act that is prohibited by Islamic criminal law. As a result, if you continue to do so, Islamic criminal law places the punishment in a ta'zir manner where the punishment follows the regulations in force in a country.